Lipid-reducing effects of sulphate-sulphide mineral water in patients with knee osteoarthritis: Abstrakt - Erceg-Rukavina, Tatjana; Dragičević-Cvjetković, Dragana (Scripta Medica, 2021)
Background / Aim: The positive effect of thermal mineral waters on human health has been known for a long time. Many pathophysiological mechanisms of action of balneotherapy are not specified. Patients with gonarthrosis often have elevated serum lipids. This study aimed to examine the effect of drinking sulphate-sulphide thermo mineral water on the lipid status of patients with gonarthrosis. Methods: A prospective clinical study followed 60 patients, both sexes, mean age 65.02 ± 1.03, with gonarthrosis. All inpatient underwent physical treatment with topical application of sulphate-sulphide mineral water. Patients of group A (N = 30) had the use of this mineral water as an additional therapy by drinking, unlike patients of group B (N = 30) who drank plain water. The level of serum lipids of these patients was monitored at admission and 4 weeks after. The variance analysis test (ANOVA) with a level of statistical significance p < 0.001 was used for statistical analysis. Results: A significant reduction in the levels of all lipid fractions in the serum of patients with gonarthrosis was found 4 weeks after the completion of inpatient physical treatment in both study groups. This decrease was statistically significant in patients of group A (p < 0.001). Conclusion: Drinking sulphate-sulphide mineral water in patients with gonarthrosis shows a positive effect on the reduction of serum lipid levels in the short-term follow-up period.